THE LEGAL STRENGTHENING IN OUR EXISTENCE INDONESIAN LAW CONSTRUCTION - Rakhmat Bowo Suharto (UNISSULA, 2020)
The concept of nationality which has been formalized juridically in the Constitution of the State and the State Constitution, is not free from examination. Starting from rebellions based on ethnicity, religion, and political ideology, the nation has experienced. The approach method uses a normative juridical approach. The approach taken to find solutions to problems of legal problems that arise is to use a statutory approach. The results of the research achieved include strengthening the law as a means as a legal system that overcomes the entire existing local legal system, the Indonesian legal system has put in place various integrating tools which are at the same time a national identity that supports pluralism in the building of the Republic of Indonesia. Law has played an important role so that the existence of the Republic of Indonesia is protected from division. The purpose of maintaining unity in order to maintain the existence of the Republic of Indonesia, the law needs to be strengthened by conducting a paradigmatic evaluation of existing legal constructs.